2017
DOI: 10.18632/oncotarget.19554
|View full text |Cite
|
Sign up to set email alerts
|

The synergistic antitumor effect of cinobufagin and cisplatin in human osteosarcoma cell line in vitro and in vivo

Abstract: Cisplatin (CDDP) has been shown to be a promising anticancer drug that is effective against many types of cancer, which include osteosarcoma (OS). However, its therapeutic application is restricted by its toxicity in normal tissues and by side effects caused in patients. Reduction of the toxicity of CDDP is necessary to improve cancer treatment. In the present study, we attempted to clarify how cinobufagin, a traditional Chinese medicine, enhances CDDP-induced cytotoxicity in OS cells. OS 143B cells were treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Compared with the effect of cisplatin alone, the combination of low-dose cisplatin significantly inhibits cell viability and motility, induces apoptosis and cell cycle arrest in the S phase, and inhibits tumor growth and metastasis, as well as prolongs the exposure of mice. Beside, longer survival time [ 17 ] in the OS xenograft model significantly inhibited the Notch signaling pathway. Gamabufotalin [ 18 ] inhibits the viability of osteosarcoma cells and tumorigenesis by blocking the TGF- β /periostin/PI3K/AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the effect of cisplatin alone, the combination of low-dose cisplatin significantly inhibits cell viability and motility, induces apoptosis and cell cycle arrest in the S phase, and inhibits tumor growth and metastasis, as well as prolongs the exposure of mice. Beside, longer survival time [ 17 ] in the OS xenograft model significantly inhibited the Notch signaling pathway. Gamabufotalin [ 18 ] inhibits the viability of osteosarcoma cells and tumorigenesis by blocking the TGF- β /periostin/PI3K/AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a large number of studies have shown that the extract of Venenum Bufonis can inhibit the proliferation of some tumor cells (29). As one of the active components of Venenum Bufonis, cinobufagin has also entered garnered interest from researchers, as it has been reported that cinobufagin can effectively inhibit the proliferation of lung cancer cells (30), liver cancer cells (17), prostate cancer cells (31), and osteosarcoma cells (32) in vitro . In this study, we investigated the effects of cinobufagin on the proliferation of A375 human malignant melanoma cells and its intrinsic mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Gavage and intraperitoneal administration of Bufonis venenum, cinobufagin and bufalin produced marked antinociception in the hot-plate, formalin and acetic acid writing tests [74,81,82]. Interestingly, Bufonis venenum has remarkable analgesic effect in patients with cancer pain including that from bone metastasis [22,50], while it has been also served as an antitumor agent [2,12,25,48]. Preclinical studies showed that multiple daily intraperitoneal injections of Bufonis venenum (referred as to cinobufagin in the original paper) exerted mechanical antiallodynia and thermal antihyperalgesia in a mouse model of paw cancer pain [9,10].…”
Section: Introductionmentioning
confidence: 99%